Kemampuan Asap Cair pada Pengawetan Ikan Bandeng Disertai Perendaman Prapengasapan dalam Larutan Mikrokapsul Oleoresin Daun Sirih - Arifan, Fahmi; Wikanta, Deddy Kurniawan; Susanti, Margaretha Tuti (INTEK: Jurnal Penelitian, 2017)
On this research have observed liquid smoke’s ability to pursue microbe activity, antimicrobe and antioxidant compounds in betel oleoresin, give preservation effect by pursue microorganism’s growth on Chanos-chanos forsk. Fish Submerge process by liquid smoke with betel oleoresin submerge on pre-smoking, give optimum result value of TVB 8,62 mg N/100gr, reach on submerge by betel oleoresin 6% concentration, during 15 minutes, and submerge with liquid smoke 4% concentration during 10 minutes. Value of total microbe 6,06 x 10 3 CFU. Result above has contribution with censor examination of rather hard texture and much liked flavor.